Assistive technology for visual impairment and trainers at schools for the blind in Delhi. Issue 4 (4th July 2022) - Senjam, Suraj Singh; Foster, Allen; Bascaran, Covadonga
ABSTRACT: The aim of the study was to assess the availability of assistive technology (AT) for visual impairment and trainers in schools for the blind in Delhi. A cross-sectional study was conducted in 22 of the 24 schools in Delhi. The headteacher of each school was asked about availability of 52 ATs divided into writing, reading, math, sciences, sports, mobility, and daily living, using a questionnaire. Information on availability of trainers was also collected. Of the 52 ATs, the most frequently available were Braille slate with stylus and abacus (>90% of schools), followed by Taylor frame, long cane and talking watch (80% to 90% of schools). Only 11 of 52 AT devices were available in 60% or more of the schools. Tactile-based ATs were more available than vision-based ATs. In the 22 schools, 63 trainers for reading & writing were available (80% of posts), 18 for sciences (59%), 25 for math (70%), and 11 for mobility (50% of posts). Except Braille slate and stylus, there is a huge shortage of AT in these schools. The educational needs and performance of students could be helped by developing and using a list of priority Assistive Products for example, the WHO AP list.